Resorbable osteosynthesis in mandibular fractures : an exploratory systematic review = Osteosíntesis reabsorbible en fracturas mandibulares : una revisión sistemática exploratoria - Sanino Zavala, Ignacio; Carrazana Díaz, Michelle; Fuentes Fernández, Darling; Guzmán Aguilera, Violeta; Quitral Argandoña, Rodrigo (2024)
Mandibular fractures have a high prevalence in the maxillofacial region, often requiring surgical intervention. The gold standard for treatment involves open reduction with osteosynthesis using titanium plates. New biocompatible materials have been applied to address the complications and disadvantages of titanium plates, leading to the emergence of absorbable osteosynthesis plates. Understanding the effectiveness of titanium plates and absorbable osteosynthesis plates in the treatment of mandibular fractures helps determine the need to invest in new techniques with predictable outcomes. To describe the effectiveness of using titanium plates and absorbable osteosynthesis plates in the treatment of mandibular fractures. In August 2023, an exploratory systematic review of the available literature since 2018 on the use of absorbable osteosynthesis plates in mandibular fractures was conducted. PubMed, Scopus, and WOS were searched, including studies in English or Spanish. A total of 227 articles were obtained. After reviewing titles and abstracts, 29 articles were included for full-text reading. Nine duplicates were discarded, and 10 were excluded based on predefined criteria, resulting in a total of 10 articles for this study. Authors report that titanium plates exhibit less displacement of the contact surface in fractured segments due to a larger surface area, rigidity, and load-bearing capacity. Absorbable osteosynthesis plates are more flexible but are susceptible to greater deformation under significant masticatory forces, potentially leading to fracture opening and displacement of bone segments. Postoperative complications were analyzed, and no statistically significant differences were found. Titanium and absorbable devices did not differ in terms of biomechanical behavior and postoperative complications in the treatment of mandibular fractures. Further studies comparing both types of plates in mandibular fractures are needed.
Las fracturas mandibulares poseen una alta prevalencia en el territorio maxilofacial, requiriendo, en su mayoría, resolución quirúrgica. El Gold Standard corresponde a la reducción abierta con osteosíntesis con placas de titanio. Nuevos materiales biocompatibles han sido aplicados con el fin de subsanar las complicaciones y desventajas de las placas de titanio, surgiendo las placas de osteosíntesis reabsorbibles. Conocer la efectividad de las placas de titanio y placas de osteosíntesis reabsorbibles en el tratamiento de fracturas mandibulares permite determinar la necesidad de invertir en nuevas técnicas con resultados predecibles. Describir la efectividad del uso de placas de titanio y placas de osteosíntesis reabsorbibles en el tratamiento de fracturas mandibulares. Durante agosto del año 2023, se realizó una revisión sistemática exploratoria de la literatura disponible desde 2018 sobre el uso de placas de osteosíntesis reabsorbibles en fracturas mandibulares, empleándose los buscadores PubMed, Scopus y WOS incluyendo estudios en inglés o español. Se obtuvieron 227 artículos. Después de la revisión de título y resumen, 29 fueron incluidos para lectura de texto completo, se descartaron 9 duplicados, 10 fueron descartados por criterios de exclusión, quedando en total 10 artículos en este estudio. Autores relatan menor desplazamiento de la superficie de contacto de las placas de titanio en los segmentos fracturados, por una mayor área de presión superficial, rigidez y fuerza de carga. Las placas de osteosíntesis reabsorbibles son más flexibles y están sujetas a mayor deformación ante fuerzas masticatorias de gran magnitud, pudiendo generar apertura de la fractura, desplazamiento de segmentos óseos. Se analizaron las complicaciones post operatorias y no presentan diferencias estadísticamente significativas. Los dispositivos de titanio y reabsorbibles no difirieron en términos de comportamiento biomécanico y complicaciones...
En revista Odóvtos, vol. 26, no.3 (setiembre-diciembre 2024)
Descripción basada en el contenido visto el 07 de febrero, 2025
También disponible en formato HTML y EPUB